2015
DOI: 10.1021/acs.langmuir.5b00970
|View full text |Cite
|
Sign up to set email alerts
|

Cu2O Nanoparticles Anchored on Amine-Functionalized Graphite Nanosheet: A Potential Reusable Catalyst

Abstract: Synthesis of Cu2O-amine-functionalized graphite nanosheet (AFGNS) composite has been accomplished at room temperature. In the first step, AFGNS is synthesized by wet chemical functionalization where the -NH2 groups formed on nanosheet surface help to anchor the Cu(2+) ions homogeneously through coordinate bonds. Reduction of Cu(2+) (3.4 × 10(-2) mmol) in the presence of NaBH4 (1.8 mmol) can be restricted to Cu(1+) on AFGNS surface at room temperature. This leads to the formation of uniform Cu2O nanoparticles (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
69
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 59 publications
8
69
0
Order By: Relevance
“…Spectral fitting reveals that the surfaces of both hierarchical materials predominantly comprise Cu 2 O (Table S1) with that of the nanocomposite somewhat enriched (88 % versus 79 %). Corresponding C 1s XP spectra revealed almost identical distributions of three distinct chemical environments for both hierarchical materials at 284.6, 286.2, and 288.3 eV (Figure b), respectively assigned to the alcohol and ether functions of PEG and surface carbonate . A small increase in the sp 2 carbon environment was observed for the Cu 2 O/rGO nanocomposite consistent with graphene incorporation (Table S2) .…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…Spectral fitting reveals that the surfaces of both hierarchical materials predominantly comprise Cu 2 O (Table S1) with that of the nanocomposite somewhat enriched (88 % versus 79 %). Corresponding C 1s XP spectra revealed almost identical distributions of three distinct chemical environments for both hierarchical materials at 284.6, 286.2, and 288.3 eV (Figure b), respectively assigned to the alcohol and ether functions of PEG and surface carbonate . A small increase in the sp 2 carbon environment was observed for the Cu 2 O/rGO nanocomposite consistent with graphene incorporation (Table S2) .…”
Section: Resultsmentioning
confidence: 76%
“…Indeed, graphite and rGO nanosheets have been explored as supports for dispersing Cu 2 O and TiO 2 respectively. Carbonaceous supports are reported to facilitate photoexcited charge separation, and hence improve the photocatalytic activity and photostability of Cu 2 O, while thin protective carbon layers arising from glucose carbonisation can significantly increase the photocurrent density and photostability of Cu 2 O for photoelectrochemical water splitting …”
Section: Introductionmentioning
confidence: 99%
“…Further, the graphitic carbon support can electronically interact with metal NPs thus improving the intrinsic property of the NPs. The synergistic effect of this interaction through transport of electrons between the two systems improves the electrical properties of the composites significantly and increases the electrical conductivity of the bulk materials as a whole …”
Section: Resultsmentioning
confidence: 99%
“…Recently, reduction of dyes in presence of NaBH 4 is considered as an affordable, effective, environment friendly technology in removing such organic pollutants in solution . Moreover, it is reported that compared to parent dyes, its reductive products become inclined to biodegradation and mineralization, largely reducing the harm to the environment . Thus, there is a growing need for developing novel methods for the reduction of organic dyes …”
Section: Introductionmentioning
confidence: 99%
“…[38] Moreover, it is reported that compared to parent dyes, its reductive products become inclined to biodegradation and mineralization, largely reducing the harm to the environment. [39][40][41][42] Thus, there is a growing need for developing novel methods for the reduction of organic dyes. [37] Herein, hetero-nanostructured Ni/a-Mn 2 O 3 catalyst was synthesized via surfactant aided co-reduction method using CTAB (surfactant) as the stabilizer for the Ni nanoparticles and NaBH 4 as reducing agent.…”
Section: Introductionmentioning
confidence: 99%